Er:YAG Laser Versus Systemic Metronidazole as an Adjunct to Nonsurgical Periodontal Therapy: A Clinical and Microbiological Study - KADİR, TANJU (MARY ANN LIEBERT INC, 2012)
Objective: The objective of this randomized clinical trial was to describe the clinical and microbiological results obtained by treatment with Er:YAG laser and systemic metronidazole used as adjuncts to mechanical subgingival debridement in chronic periodontitis. Methods: Twenty-seven chronic periodontitis (CP) patients were randomly divided into three parallel groups each comprising nine individuals with at least four teeth having at least one approximal site with a probing depth (PD) of >= 5 mm and gingival index (GI) of >= 2 in each quadrant. Groups of patients received: (1) Scaling and root planing (SRP) + Er:YAG laser (10 hz, 30 mJ/pulse, 1 min per pocket, apico-coronal direction in parallel paths with 30 degree angle tips, under water irrigation), (2) SRP + systemic metronidazole, or (3) SRP alone. In all treatment groups, SRP was performed at 1 week intervals in two sessions. The microbiological and clinical effects of the treatments were evaluated after 90 days. Results: At the end of the experimental period, statistically significant improvements in plaque index, GI, PD and attachment level, as well as reductions in the number of total bacteria and proportions of obligately anaerobic microorganisms were observed within each group. Although intergroup comparisons revealed no significant microbiological differences, clinical parameters as attachment gain and PD reduction were found significantly higher in Group 1 compared with the other groups. Conclusions: Within its limits, this study demonstrated the possibility of better resolution of infection with combined SRP + Er: YAG laser treatment. However, microbiological results failed to demonstrate significant advantages of this combination in comparison with SRP alone or SRP + systemic metronidazole.
Keywords: ER-YAG LASER; HUMAN GINGIVAL FIBROBLASTS; UP SPLIT-MOUTH; INTERLEUKIN-1-BETA PRODUCTION; ADULT PERIODONTITIS; ROOT SURFACES; IN-VITRO; IRRADIATION; PROLIFERATION; INHIBITION